Compressed Flexible Steel Reinforced Concrete Elements Investigation - Storozhenko, Leonid; Semko, Pavlo; Yefimenko, Olena (International Journal of Engineering and Technology, 2018)
Stress-strain state and compressed flexible steel-reinforced concrete elements resistance capacity are investigated in the work. The experiment program is complied and steel reinforced concrete elements calculations methods are analyzed. Experimental sample design drawings are shown. Raw materials physical and mechanical properties are determined. Steel reinforced-concrete elements experimental and research studies have been carried out. Coboundary dependences N-M for steel reinforced concrete elements construction method is proposed. Resistance capacity diagrams for steel reinforced concrete elements are constructed depending on the element height and the applied eccentricity. Â Â